PERSEPSI PELANGGAN GORIDE DAN GRABBIKE TERHADAP PESAN LAYANAN JASA PADA MASA PANDEMI COVID-19 - Agustiningsih, Gloria; Dema, Yosef (Jurnal Manajemen, 2022)
This research aims to determine the perception of online motorcycle service customers regarding the dominant indicators in determining service quality which communicates through service messages carried out by online transportation service companies in Indonesia running by Gojek and Grab, under brands of GoRide and GrabBike transportation services. The research method used is the descriptive comparative model. The sample selection technique in this study used purposive sampling, which consisted of 102 respondents. The statistical test used in this study is the data normality test, which aims to determine whether the data is normally distributed or not by using the one-sample Kolmogorov-Smirnov test. From the results of analysis and interpretation, it concluded that customers' assessments of the quality of GoRide and GrabBike services during the COVID-19 pandemic are still in the high or satisfactory category for their customers using their transportation services.